The complete chloroplast genome provides insight into the evolution and polymorphism of Panax ginseng - Zhao, Yongbing; Yin, Jinlong; Guo, Haiyan; Zhang, Yuyu; Xiao, Wen; Sun, Chen; Wu, Jiayan; Qu, Xiaobo; Yu, Jun; Wang, Xumin; Xiao, Jingfa (Frontiers in Plant Science, 2015)
Panax ginseng C.A. Meyer (P. ginseng) is an important medicinal plant and is often used in traditional Chinese medicine. With next generation sequencing (NGS) technology, we determined the complete chloroplast genome sequences for four Chinese P. ginseng strains, which are Damaya (DMY), Ermaya (EMY), Gaolishen (GLS) and Yeshanshen (YSS). The total chloroplast genome sequence length for DMY, EMY and GLS was 156,354 bp, while that for YSS was 156,355 bp. Comparative genomic analysis of the chloroplast genome sequences indicate that gene content, GC content, and gene order in DMY are quite similar to its relative species, and nucleotide sequence diversity of inverted repeat region (IR) is lower than that of its counterparts, large single copy region (LSC) and small single copy region (SSC). A comparison among these four P. ginseng strains revealed that the chloroplast genome sequences of DMY, EMY, and GLS were identical and YSS had a 1-bp insertion at base 5472. To further study the heterogeneity in chloroplast genome during domestication, high-resolution reads were mapped to the genome sequences to investigate the differences at the minor allele level; 208 minor allele sites with minor allele frequencies (MAF) of ≥ 0.05 were identified. The polymorphism site numbers per kb of chloroplast genome sequence for DMY, EMY, GLS, and YSS were 0.74, 0.59, 0.97, and 1.23, respectively. All the minor allele sites located in LSC and IR regions, and the four strains showed the same variation types (substitution base or indel) at all identified polymorphism sites. Comparison results of heterogeneity in the chloroplast genome sequences showed that the minor allele sites on the chloroplast genome were undergoing purifying selection to adapt to changing environment during domestication process. A study of P. ginseng chloroplast genome with particular focus on minor allele sites would aid in investigating the dynamics on the chloroplast genomes and different P. ginseng strains typing.